PENGARUH REKRUTMEN, PENGATURAN STAF DAN PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN - Nurdin, Muhammad (Jurnal Ekonomi Bisnis Manajemen Prima, 2021)
The development of tertiary education is now facing a lot of attention, especially in the current condition where there is obligation to work at least at undergraduate education level. Good quality employees are hired to advance education. So it is necessary to assess employee performance through a study conducted at the Indonesian College of Management (STIMI) Banjarmasin. This research uses quantitative research techniques. The sample is same as population, which is all existing employees (lecturers and academic staff) because of small population (overall). Data collection techniques are through statements distributed in the questionnaire. Data is analyzed by linear regression analysis. Recruitment, staffing and career developments in this study are in accordance with the real and present phenomena. When the recruitment, staffing and career developments are conducted well, it is expected to create good performances also. Therefore, it will make this institution survive sustainably in the future.